Teaching Behavior and Student Achievement - R. Kirby Barrick; Andrew C. Thoron (EDIS, 2016)
Student achievement can clearly be enhanced through effective teaching behaviors, but what kinds of teacher behaviors lead to higher achievement among learners? This 6-page fact sheet describes five different teacher behaviors that can lead to higher student achievement. These behaviors are clarity, variability, enthusiasm, task oriented and/or businesslike behavior, and student opportunity to learn criterion material. Written by R. Kirby Barrick and Andrew C. Thoron, and published by the Agricultural Education and Communication Department, January 2016.